1994
DOI: 10.1007/bf01405504
|View full text |Cite
|
Sign up to set email alerts
|

Glomus jugulare tumours: A review of 61 cases

Abstract: A retrospective study of 61 patients with glomus jugulare tumours treated at the National Hospital for Neurology and Neurosurgery, and at the Royal National Throat, Nose and Ear Hospital, London. The average age at presentation was 41.7 years. The patients were mainly treated by a posterolateral combined otoneurosurgical approach. 42/61 of the patients had total or subtotal excision of their tumours, 7/61 had partial removal and the remaining 11/61 had no operation. Only one case required a 2-staged procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 18 publications
0
64
0
1
Order By: Relevance
“…Unfortunately, signifi cant morbidities can frequently result from surgery, typically related to cranial nerves 7 and most commonly 9 through 12, including but not limited to: facial weakness or paralysis, swallowing dysfunction, taste dysfunction, autonomic dysfunction, hoarseness, weakness of neck muscles, and hearing loss or vestibular dysfunction. In the Gottfried review, the rate of new onset cranial nerve defi cits in those series providing data on cranial nerve dysfunction was approximately 58% [18,21]. In several additional older studies on resection, the cranial nerve defi cit rates are reported to vary anywhere from 22% to as high as 83%.…”
Section: Surgical Seriesmentioning
confidence: 90%
See 2 more Smart Citations
“…Unfortunately, signifi cant morbidities can frequently result from surgery, typically related to cranial nerves 7 and most commonly 9 through 12, including but not limited to: facial weakness or paralysis, swallowing dysfunction, taste dysfunction, autonomic dysfunction, hoarseness, weakness of neck muscles, and hearing loss or vestibular dysfunction. In the Gottfried review, the rate of new onset cranial nerve defi cits in those series providing data on cranial nerve dysfunction was approximately 58% [18,21]. In several additional older studies on resection, the cranial nerve defi cit rates are reported to vary anywhere from 22% to as high as 83%.…”
Section: Surgical Seriesmentioning
confidence: 90%
“…Regardless of the surgical technique, due to tumour locations, total resection is not always possible, particularly with "complex" tumours (giant tumours, multiple paragangliomas, malignant tumours, those with catecholamine secretion, or those with previous surgical or other therapies). Upon review of multiple series, such as those included in the review by Gottfried et al [15] (374 patients from 7 series) [4,6,18,[20][21][22][23], and excluding those that included more complex tumours, total resection has been achieved in about 85-96% of cases. Surgical resection rates for complex tumour rates are not quite as high, but still in the range of 83-86% [20,23].…”
Section: Surgical Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathy of the facial nerve was present in 16-23% necessitating tarsorraphy. Paresis of the VIth nerve occurred in 6%, and a hearing impairment or deafness was noticed in 4-26% [2,4,6,7,10]. After surgical removal of the tumor, it is important to keep in mind that at least 15% of the patients will not be able to have the same kind of lifestyle as they had before surgery [10].…”
Section: Discussionmentioning
confidence: 99%
“…After resection, progression-free survival was achieved in 92-94.5% (median follow-up 38-54 months) [2,17]. New LCNP occurred in 57% [34]. To minimize postoperative neurologic deficits, stereotactic radiosurgery (SRS) was performed as an alternative treatment option.…”
Section: Introductionmentioning
confidence: 99%